A Study on Becker's Univalence Criteria - Maslina Darus; Imran Faisal (Abstract and Applied Analysis)
We study univalence properties for certain subclasses of univalent functions K, K2, K3, and S(p), respectively. These subclasses are associated with a generalized integral operator. The extended Becker-typed univalence criteria will be studied for these subclasses.